2015
DOI: 10.1016/j.humov.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Informational constraints on spontaneous visuomotor entrainment

Abstract: Past research has revealed that an individual's rhythmic limb movements become spontaneously entrained to an environmental rhythm if visual information about the rhythm is available and its frequency is near that of the individual's movements. Research has also demonstrated that if the eyes track an environmental stimulus, the spontaneous entrainment to the rhythm is strengthened. One hypothesis explaining this enhancement of spontaneous entrainment is that the limb movements and eye movements are linked throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 93 publications
2
7
0
Order By: Relevance
“…The effect of SRC on the stability was weak, only emerging when the sequence was sped up to 400 ms IOI. The results are consistent with the previous reports on visuomotor tracking that found that the difference in stability between the S-R in-phase (compatible) pattern and the S-R antiphase (incompatible) pattern increased progressively with the increasing sequence rate (Varlet, Coey, Schmidt, & Richardson, 2012; Varlet, Bucci, Richardson, & Schmidt, 2015). The influence of sequence rate on SRC effect might reflect the limitation of information transfer rate from the visual system to motor system in the common representational medium.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of SRC on the stability was weak, only emerging when the sequence was sped up to 400 ms IOI. The results are consistent with the previous reports on visuomotor tracking that found that the difference in stability between the S-R in-phase (compatible) pattern and the S-R antiphase (incompatible) pattern increased progressively with the increasing sequence rate (Varlet, Coey, Schmidt, & Richardson, 2012; Varlet, Bucci, Richardson, & Schmidt, 2015). The influence of sequence rate on SRC effect might reflect the limitation of information transfer rate from the visual system to motor system in the common representational medium.…”
Section: Discussionsupporting
confidence: 93%
“…Our motion capture results reinforced one common finding: individuals tend to entrain their movements to a visual rhythm (Clayton, 2007;Kotz et al, 2014;Schmidt et al, 2007;Schmidt & Turvey, 1994;Varlet et al, 2015). But this uninstructed visuomotor entrainment of the head does not appear to be increased by the amplitude of the visual stimulus, at least in a multisensory context such as music performance.…”
Section: Discussionsupporting
confidence: 84%
“…Past research has provided evidence of synchronization of an individual's limb movements and posture with environmental rhythms in the presence of visual queues and during social settings (Roerdink et al, 2008;Varlet et al, 2011Varlet et al, , 2015. In the present study, the model building process involved testing models with random intercept terms for the effect of group.…”
Section: Effect Of Music and Fractality On Head Swaymentioning
confidence: 98%